SIFAT FISIK TANAH PADA HUTAN PRIMER DAN PADANG PADEHA DI DALAM KAWASAN TAMAN NASIONAL LORE LINDU - Lasa, Lasa; Wardah, Wardah; Yusran, Yusran (ForestSains, 2018)
Primary Forest and Imperata cylindrica grasslands are two different ecosystems that meet in the same area in Lore Lindu National Park. Climatic conditions such as rainfall are also the same. The difference in vegetation between the two ecosystems is interesting to be investigated by comparing the physical properties of the two ecosystems. This study aims to determine the physical properties of soils in the Primary forest and Padeha grasslands in the Lore Lindu National Park Area. This research was conducted from January to March 2017, located in the Lore Lindu National Park, Sedoa Village, Lore Utara District, Poso Regency, Central Sulawesi. This research was started from a field survey, determining the location of sampling, soil sampling, analysis of soil samples in the Laboratory. Determination of the location is done intentionally (purposive sampling) by considering the slope conditions namely, valley back and hill. Soil sampling was carried out at two depths namely 0-30 cm and 30-60 cm. Soil in primary forest has physical properties as follows: clay soil texture, medium granular and coarse granular soil structure, high bulk density 1.2 gr / cm3 and very high 1.5 gr / cm3, good soil porosity 54.5% and less good 43.6%, moderate soil permeability 5.12 cm / hour and 0.57 cm / hour rather slowly, and the color of the soil is dark yellowish, yellowish brown, strong brown. Soil in Padeha grasslands has the following physical properties: clay soil texture, rough granular soil structure and medium granular soil, high bulk density 1.3 gr / cm3 and very high 1.4 gr / cm3, good porosity 50.3% and bad 35 , 9%, moderate permeability 2.2 cm / hour and rather slow 1.46 cm / hour, and the color of the soil is strong brown, brown, and black.